Gold(I)‐Catalyzed Tandem Transformation with Diynes: Rapid Access to Linear Cyclopentenone‐Fused Polycyclic Molecules1. (16th July 2015) - Yu, Congjun; Chen, Bin; Zhou, Tian; Tian, Qingshan; Zhang, Guozhu
Abstract An efficient and convenient synthesis of useful linear cyclopentenone‐fused polycyclic compounds has been achieved through a novel gold(I)‐catalyzed transformation of diynes. The method demonstrates high product yields and tolerates of a wide variety of important functional groups. Gold‐vinylidene formation, methoxy group migration, and Nazarov‐type cyclization are proposed to be the key steps in the reaction pathway. The synthetic utility of this method is demonstrated by converting the product to eight‐membered‐ring‐fused compound.